States Interests and the Politics of Migration: Controversy of the Global Compact for Migration - Ritiauw, Daniel Areldy (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2022)
The establishment of Global Compact for Migration (GCM) was considered as the first important step for the international community to comprehensively address the issue of global migration. However, there are certain objectives within the compact that is considered as vague and unfavourable by several states. Previous studies have explored the advantages and disadvantages of GCM but did not address the specific argumentation that creates disagreements between states. This paper uses the theoretical approach from realist perspective to investigate how certain stipulations within the compact are in contrary to certain actors’ interests, specifically the interests of key state actors in global migration governance. Using qualitative methodology, the analysis began by exploring stances of notable states that opposes the compact. The findings discovered that the GCM failed to recognise the core problem of migration itself which is the management of regular and irregular migrants. The result of the study indicates that states’ rejection towards the Global Compact for Migration are mainly driven by the incompatibility of the compact’s goals and objectives with their national interest, particularly concerning sovereignty and national security.